When rural lives are reduced to staying alive - Shah, Mansi; Bhavsar, Chhaya; Ringler, Claudia (All India Disaster Mitigation Institute (AIDMI), 2021)
A recent IFPRI blog pointed to the perils of COVID-19 ravaging rural areas in second and third waves. That blog focused on the key rural risk factors of lack of access to water and health services as well as to the larger and elder populations in many rural areas.